Study of the thermoacoustic effect in an oscillating flow - Ker, Hin Ho (2018)
Thermoacoustic engines have received many attention because of the lack of moving parts and environmental benefits. The lack of moving parts means less mechanical damage, lesser wear and tear leading to lower maintenance cost and is revolutionary in future. However, past researches shows the lack of information of such engine when performing at high amplitudes. Thus, the present experimental study studies the thermoacoustic effect in an oscillating flow. It will be conducted through a model of thermoacoustic refrigerator, with a loudspeaker powered by an amplifier into a duct, using air as the medium. The sound produced by the loudspeaker causes vibration and pressure in the duct. The experiment studies pressure variation throughout the duct. The resonance frequency is first determined, in order to perform the experiment at the highest amplitude and subsequent test will be performed at the resonance frequency. Stack will then be introduced to study the thermoacoustic effect with the generation of a temperature difference from the supplied acoustic energy. And lastly, the position of the stack will be varied to determine the effect of position on stack performance. Future work should be conducted to understand the flow field happening inside the stack so as to improve the efficiency of thermoacoustic devices.